2022
DOI: 10.4136/ambi-agua.2868
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of the beet crop under agricultural environment and saline stress

Abstract: The deleterious effects of salts on plants exposed to high solar radiation tend to be more accelerated due to the increase of toxic ions in the aerial plant part. Consequently, the physiological and biochemical processes will be affected. These effects can be minimized, however, with the use of management strategies, such as the use of a shading screen and a protected environment. In this sense, the objective of this work was to evaluate the physiological responses of sugar beet cultivated in different environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…These same authors found no mitigating effect on photosynthesis at 45 days after sowing. However, a similar trend for sugar beet was reported by [9], when using 100% phosphate fertilization in a saline environment.…”
Section: Leaf Gas Exchangesupporting
confidence: 83%
See 3 more Smart Citations
“…These same authors found no mitigating effect on photosynthesis at 45 days after sowing. However, a similar trend for sugar beet was reported by [9], when using 100% phosphate fertilization in a saline environment.…”
Section: Leaf Gas Exchangesupporting
confidence: 83%
“…Comparing phosphate fertilization in the presence of Trichoderma and water with a higher salinity (6.2 dS m −1 ), there was a statistical difference between the doses of 25% of the phosphorus recommendation and those of 50% and 100%, with the highest values of transpiration in the presence of the microorganism. When the concentration of salts in the soil rises, the osmotic potential decreases, causing the plants to strategically reduce the loss of water to the environment by reducing the leaf area, as the rate of transpiration is greater than absorption [9].…”
Section: Leaf Gas Exchangementioning
confidence: 99%
See 2 more Smart Citations
“…Under saline conditions, increasing water use efficiency is a strategy employed by moderately tolerant crops to mitigate high salt concentrations in the plant area (Fernandes et al, 2016;Oliveira et al, 2022). Likewise, Sousa et al (2022) also observed reductions in WUE with increasing irrigation water salinity under 50 and 100% ETc in zucchini crop.…”
Section: Discussionmentioning
confidence: 99%